EVALUATION OF LEARNING BASED ON THE PROPHETIC VALUES OF HADITH - Pratami, Fuji; Pulungan, Nur Hamidah; Permata Sari, Novia (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2025)
This paper explores the concept of learning evaluation from the perspective of hadith using a thematic approach (mawḍūʿī) to uncover prophetic values that can be integrated into Islamic educational evaluation practices. In this context, learning evaluation is a tool for measuring cognitive achievement and a reflective process to assess the internalisation of spiritual, moral, and social values. The hadiths of Prophet Muhammad (peace be upon him) that demonstrate evaluative practices—such as giving praise, correction, feedback, reflective dialogue, and adjusting teaching strategies—serve as the normative foundation for developing a prophetic-based evaluation paradigm. From this thematic study, three core values are identified as the foundation of the prophetic approach: transcendence (awareness of divinity), humanisation (respect for human dignity), and liberation (freedom from ignorance and injustice). Evaluation in hadith is humanistic and contextual, emphasising personal transformation rather than mere numerical assessment. Thus, this study offers both conceptual and practical contributions in designing an Islamic learning evaluation model that is more holistic, transformative, and relevant to the challenges of contemporary education.